2006
DOI: 10.1086/506618
|View full text |Cite
|
Sign up to set email alerts
|

IncreasedLeishmaniaReplication in HIV‐1–Infected Macrophages Is Mediated by Tat Protein through Cyclooxygenase‐2 Expression and Prostaglandin E2Synthesis

Abstract: Protozoan parasites of the genus Leishmania frequently occur as opportunistic pathogens in human immunodeficiency virus type 1 (HIV-1)-infected individuals, but the mechanisms underlying protozoan growth in this context are poorly understood. Here, we demonstrate that the HIV-1 Tat protein drives Leishmania replication in primary human macrophages. We found that Leishmania growth doubled in HIV-1-infected macrophages and that anti-Tat antibodies reduced the exacerbated protozoan replication by 70%. Recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 45 publications
4
50
0
1
Order By: Relevance
“…Overall, these data reinforced the idea that HIV/AIDS can be a predisposing condition for VL (Cacopardo et al. 1996, Wolday et al 1999, Barreto-de-Souza et al 2006, Alvar et al 2008) and the hypothesis that VL can be a predisposing condition for HIV/AIDS progression should also be considered. Therefore, improving the epidemiological surveillance of HIV infection among VL patients may lead to a precocious diagnosis before the onset of severe immunodeficiency.…”
Section: Discussionsupporting
confidence: 75%
“…Overall, these data reinforced the idea that HIV/AIDS can be a predisposing condition for VL (Cacopardo et al. 1996, Wolday et al 1999, Barreto-de-Souza et al 2006, Alvar et al 2008) and the hypothesis that VL can be a predisposing condition for HIV/AIDS progression should also be considered. Therefore, improving the epidemiological surveillance of HIV infection among VL patients may lead to a precocious diagnosis before the onset of severe immunodeficiency.…”
Section: Discussionsupporting
confidence: 75%
“…Barreto-de-Souza et al (25) recently studied the role of the transcriptional transactivator (Tat) protein, an essential viral gene product for HIV-1 replication, in the exacerbation of Leishmania proliferation in human macrophages. Tat is secreted in large amounts by cells infected by HIV-1 and is able to stimulate secretion of IL-1␤, IL-4, IL-6, IL-8, transforming growth factor beta (TGF-␤), TNF-␣, and TNF-␤.…”
Section: Pathogenesis Vl-hiv Coinfectionmentioning
confidence: 99%
“…7,11 Leishmaniasis resolution requires an effective cellular immune response, and because immune function is particularly affected by HIV infection, it is not surprising that modifications in ATL presentation and response to treatment have been described. 7,12,13 The majority of reports of ATL/HIV-AIDS association have originated from areas of Latin America where L. ( V. ) braziliensis is the major causative parasite. It has been shown that the disease caused by L. ( V. ) braziliensis and L. ( V. ) guyanensis differs regarding clinical and therapeutic aspects.…”
Section: Introductionmentioning
confidence: 99%